Dieta de três espécies de carnívoros simpátricos no Parque Nacional Grande Sertão Veredas, MG e ecologia e comportamento do lobo-guará (Chrysocyon brachyurus, Illiger, 1815) - Ana Carolina Costa Lara Rocha (2008)
One of the most importants aspects from the animal ecology is the diet, as it bears on directly and indirectly in the social and reproductive behavior of the species, besides your distribution and density. The food habit is one of the several factors that affect in the coexistence between sympatric species being one of the most studied. For this reason the main goal is describe the diet from three species of sympatrics carnivores maded wolf (Chrysocyon brachyurus), crab-eating fox (Cerdocyon thous) e puma (Puma concolor) - that occur in the Grande Sertão Veredas National Park in the state of Minas Gerais, as the alimentar niche overlap between them. The analysis from 139 faecal samples from the maded-wolf evidenced an omnivorous and generalised diet. Wolfs fruit (Solanum lycocarpum Solanaceae) and small rodents were the items most importants both right in the great deal feces event and right the biomass consumed. The Armadilos, in spite of little common in the diet, were the third greater contributed item to biomass. There were a very striking seasonality in the consumption of the items follows: Wolfs fruit and small rodents were the most ingested during the dry season and the saputá (Salacia crassiflora Hoppocrataeceae) and arthropods, in the rainy season. The crab-eating fox diet was examined from 28 faecal samples, 24 of which were collected during the dry season. Occurred the predominance of the plants items in the feces, mainly palm tree fruits, Dugetia furfuraceae (Annonaceae) e Emmotun nitens (Icacinaceae) - however have been found equivalent values of animal and plant biomass. The analysis of 23 puma's feces proved a diet based in animals of big size (weight bigger than 15kg) and the incident of the littles preys like small rodents, birds and snakes. The main preys eaten, as regards to two measured guidelines, were collared peccary, followed by deer. In the Grande Sertão Veredas National Park, during the dry season, was observed an ecological severance between maded-wolf and crab-eating fox has just been shown by unequal representative in the diet of some commons items at species, especially from plant-based feeds and by the distinction in the prey size eaten. This last was the element of niche's segregation between crab-eating fox, maded-wolf and puma, happening a gradient mid the predator's size and the prey eaten. According to the results obtained in these study, the Grande Sertão Veredas National Park keep a variety of food resources that are the foundation of the some predator's diet.